Optimalisasi Implementasi Sistem Informasi Administrasi Desa dalam Mewujudkan Transparansi dan Akuntabilitas Pemerintahan Desa - Wijaya, Acum; Putri, Risa Haruman; Prikurnia, Anas Khair; Oktavia, Della (CV. Tripe Konsultan, 2024)
This community service program aims to implement a village administration information system to enhance transparency and accountability in village governance. The background of this activity arises from the challenges of manual administrative practices still widely used in villages, which often cause delays in services, recording errors, and lack of public information disclosure. The implementation methods include preliminary observation, interviews, system design, software installation, training for village officials, system usage simulation, and monitoring and evaluation. The results show that the developed village administration information system successfully accelerated service processes, simplified administrative recording, and improved data accuracy. Village officials gained new skills through training and simulation, while the community obtained clearer access to public service information. Although some obstacles remain, such as limited infrastructure and lack of technological skills, this program positively impacted the effectiveness of village officials’ performance, the quality of public services, and strengthened community trust in village governance. Overall, the implementation of a village administration information system serves as a strategic step toward realizing transparent, accountable, and technology-adaptive village governance. This success is expected to be replicated in other villages as a model for administrative digitalization in support of achieving good governance principles at the village government.